PERLINDUNGAN HUKUM BAGI PEMBERI HAK TANGGUNGAN YANG BUKAN DEBITUR DALAM PERJANJIAN KREDIT - Muh Akbar Ariz Purnomo (Unnes Law Journal, 2014)
Dewasa ini hampir setiap pertumbuhan ekonomi didukung dengan adanya jasa perbankan. Setiap perjanjian kredit harus menggunakan jaminan sebagai syarat pengajuan kredit. Jaminan yang diberikan debitur kepada bank sangat beragam jenis namun yang sering digunakan jaminan berupa tanah. Berdasarkan observasi di BPR Jateng Cabang Gubug periode Januari tahun 2012 hingga Juli tahun 2013 terdapat 85 debitur atau 71% menggunakan tanah milik sendiri dan 34 debitur atau 29%  menggunakan tanah milik orang lain dari total 119 debitur yang menggunakan jaminan tanah. Dari jumlah tersebut dapat dikatakan bahwa di BPR Jateng Cabang Gubug debitur sering menggunakan tanah milik orang lain sebagai jaminan untuk pelunasan atas kreditnya. Penelitian ini menggunakan metode pendekatan yuridis sosiologis, dengan menggunakan data primer dan data sekunder yang kemudian dianalisis dengan menggunakan analisis data kualitatif untuk mengetahui prosedur pembebanan Hak Tanggungan dalam hal pemberi Hak Tanggungan bukan sebagai debitur dalam perjanjian kredit di BPR Jateng cabang Gubug Kabupaten Grobogan dan  perlindungan hukum bagi pemberi Hak Tanggungan yang bukan debitur. Hasil dari penelitian ini adalah proses pembebanan Hak Tanggungan di BPR Jateng Gubug melalui beberapa tahap yang sesuai dengan prosedur pembebanan Hak Tanggungan. Perlindungan hukum terhadap pemberi Hak Tanggungan yang bukan debitur sudah dilakukan namun masih lemah. Today every economic growth is supported by the presence of banking services. Each loan agreement must use the collateral as a condition for obtaining loans. Guarantees that debtors given to bank more varied but are often used type of collateral such as land. Based on the observation in the BPR Jateng Cabang Gubug period from January 2012 to July of 2013 there were 85 or 71 % of the debtor 's own land use and 34 debtor or 29 % use someone else's land of a total of 119 debtors who use the land collateral. Of this amount can be said that in the BPR Jateng cabang Gubug, debtors often use someone else's land as security for the repayment of the above loan. It’s necessary for transparency in the legal protection for Mortgage providers are not debtors in the credit agreement in BPR Jateng Cabang Gubug Kabupaten Grobogan. The problems of this study are 1) What is the procedure of loading Mortgage in terms Mortgage providers are not as a debtor under the credit agreement in the BPR Jateng cabang Gubug Kabupaten Grobogan? 2) What legal protection for Mortgage providers are not as a debtors in the credit agreement in the BPR Jateng cabang Gubug Kabupaten Grobogan when the debtor defaults? This study uses a socio-juridical approach, using primary data and secondary data were then analyzed using qualitative data analysis. The results of this study are in the process of loading Mortgage BPR Jateng cabang Gubug Kabupaten Grobogan through several stages according to the Mortgage loading procedure. Legal protection of Mortgage providers are not the debtor has been done but still weak. The conclusions in this study were 1) the loading Mortgage procedure in the BPR Jateng cabang Gubug through three stages, namely making the credit agreement, granting Mortgage and Mortgage registration,  2) protection of the law giver Mortgage borrowers are divided into preventive legal protection and protection law if the debtor defaults. Suggestion that researchers give is 1) the government is expected to be watched, simplify and reduce the cost of registration Mortgage. Besides, the government is also expected to consider the legal protection of Mortgage providers are not the debtor. 2) BPR Jateng cabang Gubug Kabupaten Grobogan expected to be more careful and check the details before the certificate is registered Mortgage and more selective in choosing potential borrowers and collateral objects. 3 ) Mortgage Providers should be cautious when lending certificates to others as collateral under the credit agreement and undertake preventive measures against theirself  by making a written agreement with the debtor personally as a precaution if the debtor defaults.